ANALYSIS OF MURABAHAH FINANCING FOR GOLD INSTALLMENT PRODUCT AT BANK SYARIAH INDONESIA BRANCH OFFICE MAGELANG GATOT SUBROTO - Erissa Zumarnis; Chaidir Iswanaji; Nibras Anny Kahbibah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study aims to investigate the implementation of Murabahah financing, the challenges encountered in implementing Murabahah financing, and the strategies employed to overcome these obstacles at Bank Syariah Indonesia Magelang Gatot Subroto Sub-Branch Office. The research utilizes both secondary and primary data, with data collection techniques including interviews. The study adopts a qualitative research approach. The findings reveal that the Murabahah Agreement is established when a customer wishes to purchase gold from the bank in installments over an agreed period of time. The term "gold installments" is used to market the bank's gold installment financing products to customers. The bank will order the desired type of gold from PT. ANTAM once the customer's installments are fully paid. The bank then delivers the goods or gold to the customer in accordance with the initial agreement stated in the contract. This practice is implemented by the bank to mitigate potential risks. The challenges faced by Bank Syariah Indonesia at Magelang Gatot Subroto Sub-Branch Office involve promoting gold installment products. To address these challenges, the marketing team must regularly update the gold installment brochure using social media or other promotional platforms to enhance effectiveness. This is crucial due to the daily fluctuations in gold prices. The bank undertakes these efforts to ensure that customers are constantly informed about the latest gold price percentages